2011
DOI: 10.1055/s-0030-1271218
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Pneumatosis in a Premature Neonate

Abstract: Gastric pneumatosis is extremely rare during infancy. It has been reported in association with necrotizing enterocolitis or congenital abnormalities such as pyloric stenosis. Here, we report a case of gastric pneumatosis in a premature neonate on synchronized nasal intermittent positive pressure ventilation. No pneumatosis was noted in the rest of the bowel or esophagus. There could have been mild damage in the gastric mucosa, either related to the placement of the feeding tube or secondary to the use of indom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Increase in intragastric pressure and dilatation of the stomach has been reported, after positive pressure ventilation without tracheal intubation, possibly due to high cricopharyngeal pressures. The rise of intragastric pressure by NIMV in a damaged gastric mucosa after ibuprofen use can cause submucosal dissection of air as noted in our case 1. Ibuprofen is a well-recognised drug that causes gastric and intestinal mucosal injury.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Increase in intragastric pressure and dilatation of the stomach has been reported, after positive pressure ventilation without tracheal intubation, possibly due to high cricopharyngeal pressures. The rise of intragastric pressure by NIMV in a damaged gastric mucosa after ibuprofen use can cause submucosal dissection of air as noted in our case 1. Ibuprofen is a well-recognised drug that causes gastric and intestinal mucosal injury.…”
Section: Discussionsupporting
confidence: 53%
“…Cyanotic heart disease has been linked to GP in a neonate with hypoplastic left heart syndrome by Krueger et al ,17 non-invasive ventilation such as NIMV is one of the causes of gastric emphysema, especially in face of ischaemic mucosa. Ting et al reported a case of gastric pneumatosis associated with the use of indomethacin in a preterm neonate while on synchronised NIMV 1. Increase in intragastric pressure and dilatation of the stomach has been reported, after positive pressure ventilation without tracheal intubation, possibly due to high cricopharyngeal pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated that there was a mild damage in the gastric mucosa, due to the placement of the feeding tube or the use of indomethacin or both together. They believed that noninvasive ventilation increased the intragastric pressure that resulted in the submucosal dissection of air followed by the development of gastric pneumatosis [7]. In our patient, the exact cause of gastric pneumatosis remains unclear.…”
Section: Clinical Imagesmentioning
confidence: 73%
“…Amongst the several postulated theories for the development of gastric emphysema in infancy secondary to obstruction, mucosal damage due to mechanical pressure developed in the distal obstruction is at the forefront. A tear in the mucosa is thought to be the cause for air tracking in the submucosa leading to emphysema [10,15].…”
Section: Discussionmentioning
confidence: 99%